Cholesterol affects the binding of proteins to phosphatidic acid without influencing its ionization properties - Desmond Owusu Kwarteng; Alexander Wolf; Madisyn Langdon; Nawal Kassas; Nicolas Vitale; Edgar Eduard Kooijman (Journal of Lipid Research)
Phosphatidic acid (PA) through its unique negatively charged phosphate headgroup binds to various proteins to modulate multiple cellular events. To perform such diverse signaling functions, the ionization and charge of PA's headgroup rely on the properties of vicinal membrane lipids and changes in cellular conditions. Cholesterol has conspicuous effects on lipid properties and membrane dynamics. In eukaryotic cells, its concentration increases along the secretory pathway, reaching its highest levels toward the plasma membrane. Moreover, membrane cholesterol levels are altered in certain diseases such as Alzheimer's disease, cancer, and in erythrocytes of hypercholesteremia patients. Hence, those changing levels of cholesterol could affect PA's charge and alter binding to effector protein. However, no study has investigated the direct impact of cholesterol on the ionization properties of PA. Here, we used 31P MAS NMR to explore the effects of increasing cholesterol concentrations on the chemical shifts and pKa2 of PA. We find that, while the chemical shifts of PA change significantly at high cholesterol concentrations, surprisingly, the pKa2 and charge of PA under these conditions are not modified. Furthermore, using in vitro lipid binding assays we found that higher cholesterol levels increased PA binding of the Spo20p PA sensor. Finally, in cellulo experiments demonstrated that depleting cholesterol from neurosecretory cells halts the recruitment of this sensor upon PA addition. Altogether, these data suggest that the intracellular cholesterol gradient may be an important regulator of proteins binding to PA and that disruption of those levels in certain pathologies may also affect PA binding to its target proteins and subsequent signaling pathways.